Glucocorticoid‐Induced Insulin Resistance in Men Is Associated With Suppressed Undercarboxylated Osteocalcin. (17th September 2018) - Parker, Lewan; Lin, Xuzhu; Garnham, Andrew; McConell, Glenn; Stepto, Nigel K; Hare, David L; Byrnes, Elizabeth; Ebeling, Peter R; Seeman, Ego; Brennan‐Speranza, Tara C; Levinger, Itamar
ABSTRACT: In mice, glucocorticoid‐induced insulin resistance occurs largely through impaired osteoblast function and decreased circulating undercarboxylated osteocalcin (ucOC). Whether these mechanisms contribute to glucocorticoid‐induced insulin resistance in humans has yet to be established. In addition, the effects of glucocorticoids on the exercise‐induced increase in circulating ucOC and insulin sensitivity are also unknown. We hypothesized that acute glucocorticoid treatment would lead to basal and postexercise insulin resistance in part through decreased circulating ucOC and ucOC‐mediated skeletal muscle protein signaling. Nine healthy men completed two separate cycling sessions 12 hours after ingesting either glucocorticoid (20 mg prednisolone) or placebo (20 mg Avicel). The homeostatic model assessment was used to assess basal insulin sensitivity and a 2‐hour euglycemic–hyperinsulinemic clamp was commenced 3 hours after exercise to assess postexercise insulin sensitivity. Serum ucOC and skeletal muscle protein signaling were measured. Single‐dose glucocorticoid ingestion increased fasting glucose (27%, p  < 0.01) and insulin (83%, p  < 0.01), and decreased basal insulin sensitivity (−47%, p  < 0.01). Glucocorticoids reduced insulin sensitivity after cycling exercise (−34%, p  < 0.01), reduced muscle GPRC6A protein content (16%, p  < 0.05), and attenuated protein phosphorylation of mTOR Ser2481, Akt Ser374, and AS160 Thr642 (59%, 61%, and 50%, respectively; all p s < 0.05). Serum ucOC decreased (−24%, p  < 0.01) which correlated with lower basal insulin sensitivity ( r  = 0.54, p  = 0.02), lower insulin sensitivity after exercise ( r  = 0.72, p  < 0.05), and attenuated muscle protein signaling ( r  = 0.48–0.71, p  < 0.05). Glucocorticoid‐induced basal and postexercise insulin resistance in humans is associated with the suppression of circulating ucOC and ucOC‐linked protein signaling in skeletal muscle. Whether ucOC treatment can offset glucocorticoid‐induced insulin resistance in human subjects requires further investigation. © 2018 American Society for Bone and Mineral Research.